ECOLITERACY MASYARAKAT RAWAN BENCANA MELALUI MITOS PRABU BOKO DI KECAMATAN TAWANGMANGU, KABUPATEN KARANGANYAR, JAWA TENGAH (Forum Ilmu Sosial, 2013)
This study aims to consider about ecoliteracy in community with sensitive natural disaster by local knowledge “Prabu Boko Mithology”. Existence of the myth could cause a holy placed at neighborhood had “danyang” as ancestor taking care village. To respect “danyang”, community run traditional ritual to refuse natural disaster. The data are gained by indepth interview through public figure, religious man, and caretaker holy placed. Moreover, this study is run by non participant observation and folklore (traditional story) to reinforce the data. Based on the data show that traditional community still have been believe on Prabu Boko Myth by done “Bersih Desa” ritual with rituals offering as respect of ancestor. “Bersih Desa” means traditional ritual to repeal natural disaster.